25 Years of the Onchocerca ochengi Model. Issue 12 (December 2016) - Makepeace, Benjamin L.; Tanya, Vincent N.
Abstract : Although of limited veterinary significance, Onchocerca ochengi has become famous as a natural model or 'analogue' of human onchocerciasis (river blindness), which is caused by Onchocerca volvulus . On the basis of both morphological and molecular criteria, O. ochengi is the closest extant relative of O. volvulus and shares several key natural history traits with the human pathogen. These include exploitation of the same group of insect vectors (blackflies of the Simulium damnosum complex) and formation of collagenous nodules with a similar histological structure to human nodules. Here, we review the contribution of this natural system to drug and vaccine discovery efforts, as well as to our basic biological understanding of Onchocerca spp., over the past quarter-century. Trends: The Onchocerca ochengi system has consistently shown that strong, albeit incomplete, natural immunity exists in cattle and that partial protection can be induced by both irradiated and recombinant vaccines. In accordance with human data, the O. ochengi system has demonstrated that Wolbachia induce a profound local neutrophilia within nodules. Recent proteomic data obtained from nodule fluid showed that adult worms are 'bathed' in liberated neutrophil granule contents, especially antimicrobial proteins. The Wolbachia endosymbiont of O. ochengi has a highly reduced genome that can produce few vitamins and cofactors, although it may generate energy in the form of ATP for its host. The most abundant Wolbachia proteins induce neutrophil activation and chemokinesis. Small RNAs with diagnostic potential are released by Onchocerca spp. into nodule fluid and human (and bovine) blood.